Performance Analysis of Wireless Cooperative Networks with Iterative Incremental Relay Selection - S. Poursajadi; M. H. Madani (AUT Journal of Electrical Engineering)
In this paper, an iterative incremental relay selection (IIRS) scheme is considered for wireless cooperative networks in order to increase the reliability of transmission. Different from the conventional incremental relay selection which incrementally selects a best relay for only one iteration; the IIRS scheme iteratively applies the incremental relaying and relay selection processes. To evaluate the performance of the proposed scheme, outage probability and average capacity of the system are investigated through analysis and simulation. This scheme provides (I+1) diversity order in a system of I relays as the highest diversity order which can be provided by all participate (AP) cooperative scheme. Also, it is shown that the IIRS scheme combats with the spectral efficiency loss resulted by applying all of the relays. As the cost of improvement, it is seen that the average required feedback bits to implement the IIRS scheme leads to I*log2(I+1) bits at low signal to noise ratio (SNR), while it leads to log2(I+1) bits at higher SNRs which is acceptable for implementation. Considering the provided improvement along with the limited feedback reveals that the IIRS scheme can be applied as an efficient scheme compared to the other common cooperative schemes. Finally, numerical results indicate the validity of the analysis especially at high SNRs.